Management of bladder exstrophy in an adolescent girl: a case report (Medical Journal of Indonesia, 2022)
Bladder exstrophy (BE) is a very rare congenital abnormality, especially in girls. We reported a 17-year-old girl with protruded bladder and urinary incontinence. Her vaginal orifice appeared stenotic and shifted anteriorly. She had an incomplete labia minora, short perineum, and anterior displacement of the anus. The pelvic radiography showed a pubic diastasis with a manta ray sign, and the ultrasonography examination showed a bicornuate uterus. She had undergone a functional reconstruction surgery with cystectomy, ileal conduit, appendectomy, and vaginoplasty along with the advancement of abdominal flap reconstruction with multiple Z-plasty. Functionally, she was able to urinate through the ileal conduit comfortably, had a regular menstrual cycle with minimal pain, had a wider vaginal canal, and had a smooth blood flow. Aesthetically, she had a good lower abdomen appearance, remained dry, and had an odorless urine. In clinical practice, this rare case report can provide additional knowledge and management of the same cases with effective results.